TWIN TRAWLING FOR SHRIMP WITH DUMMY DOOR - RAMARAO, S V.R; MATHAI, P GEORGE; PANICKER, P A (Fishery Technology, 2017)
Twin trawling; a new concept in shrimp trawling is describedin this paper. lt essentially involves towing of two trawlsof equal size connected in sequence at the inner head andfoot rope legs and using a pair of outer otter boards andcentral neutral door or dummy door with triple bridles andsingle tow warp. A comparative study with conventional sterntrawling using a standard 13.7 m. four seam shrimp trawl andtwo 6 8 m. standard four seam trawls as twin-•1g has shownconsiderable reduction in Lle utilizat.un cf 1--ower (20 %) withbetter eft!ciency in shrimp fishing.